Security and Interorganizational Networks in Peace Operations - Akbulut-Gok, Isil. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers a comprehensive analysis of preconditions and processes of interorganizational cooperation among IGOs in peace operations and how these collaborative efforts account for the success and failure of such missions. The author bases its conclusion on insights from social network analysis and an in-depth review of three cases of inter-IGO collaboration in intrastate conflicts: Violence abatement in Ivory Coast, conflict containment in Bosnia and conflict settlement in Darfur. This project will be beneficial for both policy and scholarly communities. By studying the empirical record of cooperation in peace operations, this work sheds light on best practices and makes specific policy recommendations for IGOs engaged in peace missions. Isil Akbulut-Gok is Associate Professor at the Department of Government, Sacred Heart University, USA. .
Chapter 1: Introduction -- Part I: Theory Development -- Chapter 2: Theory of Interorganizational Collaboration and Network Effectiveness -- Chapter 3: Effects of Inter-IGO Networks on Peace Operation Outcomes -- Part II: Cases -- Chapter 4: Violence Abatement Success in Ivory Coast -- Chapter 5: Conflict Containment Success in Bosnia -- Chapter 6: Conflict Settlement Success in Darfur -- Chapter 7: Conclusion.
Keywords: Security, International; Politics and war; Peace; International Security Studies; Military and Defence Studies; Peace and Conflict Studies